2010
DOI: 10.1099/jmm.0.020339-0
|View full text |Cite
|
Sign up to set email alerts
|

DnaK and GroEL are induced in response to antibiotic and heat shock in Acinetobacter baumannii

Abstract: We studied the expression of DnaK and GroEL in Acinetobacter baumannii cells (strains ATCC 19606 and RS4) under stress caused by heat shock or antibiotics. A Western blot assay showed that DnaK and GroEL levels increased transiently more than 2-fold after exposure of bacterial cells to heat shock for 20 min at 50 6C. Heat induction of DnaK and GroEL was blocked completely when an inhibitor of transcription, rifampicin, was added 1 min before a temperature upshift to 50 6C, suggesting that the induction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 38 publications
5
54
0
Order By: Relevance
“…The upregulation of chaperones DnaK and GroEL has been further observed in cell stress responses, such as heat shock stress and antibiotic presence, where some association with antibiotic resistance has been established (11). In this work, we have also observed alterations in DnaK and GroEL patterns of expression in the metabolism of resistant strains in a nonstress environment.…”
Section: Discussionsupporting
confidence: 63%
“…The upregulation of chaperones DnaK and GroEL has been further observed in cell stress responses, such as heat shock stress and antibiotic presence, where some association with antibiotic resistance has been established (11). In this work, we have also observed alterations in DnaK and GroEL patterns of expression in the metabolism of resistant strains in a nonstress environment.…”
Section: Discussionsupporting
confidence: 63%
“…As described for E. coli [52] , Bacillus cereus [53] and Acinetobacter baumannii [54], in R. tropici PRF 81 the molecular chaperone GroEL was up-regulated under high temperature. The differential expression of GroEL is critical to thermotolerance, since the chaperone can routinely rescue more than 80% of a denatured protein population [55].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that GroEL/GroES up-regulation during aminoglycoside induced stress in different bacteria (8,18). Considering these observations, it seems likely that the MGM100 strain is violently impacted by aminoglycosides during arabinose omission, even if inhibition of GroEL/GroES expression leads to only limited depletion, because the natural response involving up-regulation of GroEL/GroES has been disabled.…”
Section: Chaperonin Overexpression Reduces Aminoglycoside-induced Promentioning
confidence: 92%
“…Similar findings have been reported for E. coli, implying a response to misfolded proteins following aminoglycoside exposure (3). The aminoglycoside antibiotic kanamycin has been reported to induce several heat shock proteins, including GroEL, GroES, and DnaK in E. coli (7), and streptomycinincreased expression of heat shock proteins DnaK (Hsp70) and GroEL (Hsp60) in the opportunistic human pathogen Acinetobacter baumannii (8), consistent with aminoglycoside damage triggering protein misfolding. Whether these chaperones provide protection against exposure to aminoglycosides has not previously been investigated.…”
mentioning
confidence: 96%
See 1 more Smart Citation